2015
DOI: 10.1109/tbme.2015.2427339
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Transcranial Ultrasound Stimulation Immediately After The Ischemic Brain Injury is Neuroprotective

Abstract: The noninvasiveness and high spatiotemporal resolution of pTUS makes it a unique neuromodulation technique in comparison with the current TMS and tDCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 35 publications
3
42
0
Order By: Relevance
“…Such activation results in functional and structural protection from impending ischemic stroke, findings that were independently replicated in other labs. [5][6][7][8][9][10] Further, our findings [11][12][13][14][15][16][17][18] (reviewed in Refs. [19][20][21] have demonstrated that such stimulus-based protection is achievable in anesthetized rats, unrestrained behaving rats, and in old rats.…”
Section: Introductionsupporting
confidence: 67%
“…Such activation results in functional and structural protection from impending ischemic stroke, findings that were independently replicated in other labs. [5][6][7][8][9][10] Further, our findings [11][12][13][14][15][16][17][18] (reviewed in Refs. [19][20][21] have demonstrated that such stimulus-based protection is achievable in anesthetized rats, unrestrained behaving rats, and in old rats.…”
Section: Introductionsupporting
confidence: 67%
“…Later researches utilized low-intensity ultrasound (no higher than 500 mW/cm 2 ) whose effect was reversible on modulating neuronal excitation and inhibition and avoided the thermal injury caused by high-intensity ultrasound [8,41,42]. Though still in preclinical stage, low-intensity FUS has been demonstrated to be beneficial in treating traumatic brain injury in rodent models [11,43]. Other studies showed that FUS could improve hippocampal neurogenesis in mice, suggesting its potential application in treating Alzheimer's disease and other dementia in the future [44].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, focused ultrasound stimulation (FUS) has evolved to be a noninvasive technique to modulate neuronal functions with high spatial resolution, and being able to target at small and deep brain regions due to the utilization of focused ultrasound [8][9][10][11]. Though proved to be beneficial in treating various neuronal diseases in preclinical researches, the unclear mechanisms of neuronal modulation induced by FUS made the manipulation of stimulation effects difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that many types of stimulation methods are able to modulate regional CBF, including repetitive transcranial magnetic stimulation (rTMS), deep brain stimulation (DBS), pulsed transcranial ultrasound stimulation (pTUS), and PSS. 22,[52][53][54][55] Burnett et al 53 showed that electrical forepaw stimulation (i.e., PSS) is one method that is able to decrease infarct size because the PSS-induced blood flow increase exceeds the increase in metabolic demand after middle cerebral artery occlusion (MCAo), thus preventing the infarct. Our previous studies based on a rat PTI model also indicated that both unilateral and bilateral PSS can protect brain tissues in the ischemic penumbra through reperfusion.…”
Section: Discussionmentioning
confidence: 99%